Fiqh minority for Papuan Muslims in the perspective of Maqasid al-Shari`ah - Kasdi, Abdurrohman; Wahib, Mohammad; Umma Farida,; Zada, Khamami (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article aims at describing the implementation of fiqh minority for Muslims in Papua with the perspective of Maqasid al-Shari`ah. The study used the qualitative method with the religious sociological approach considering that the study of fiqh minority has closely related to the religious development of the Papuan people. The results reveal that fiqh minority can be a solution for the Muslim minority community throughout Papua in practicing the teachings of Islam and living peacefully with the other adherent religions. The implementation of fiqh minority in the perspective Maqasid al-Shari`ah is closely related to the protection of Muslim minorities in predominantly non-Muslim areas. Some cases of applying the fiqh minority in Papua are related to the impurity of dog fur, saying Merry Christmas, the application of political fiqh, and marrying women of the Ahl al-Kitab such as Jews and Christians.